When You Care Enough to Pay Someone to Send the Very Best: The Outsourcing of Greeting Card Inscriptions. Issue 1 (5th December 2016) - Lair, Craig D.
Abstract : It is now possible for individuals and businesses to hire a service to inscribe, by hand, the greeting cards they send. Based on a content analysis of Web sites that provide this service, and drawing from the ideas of Erving Goffman, I argue that beyond simply writing cards for their clients, what these providers ultimately offer them is the ability to be presented as someone who performed a particular presentation ritual (i.e., the sending of a card with a personal inscription) for another when, in fact, they did not. This can be seen in terms of how outsourced inscriptions are presented as ones that have not been outsourced and/or how many providers employ defensive practices seemingly designed to prevent recipients from discovering that an inscription was outsourced. As such, a kind of misrepresentation seems necessary if outsourced inscriptions are to have all the instrumental and symbolic benefits the providers of this service claim they offer. Some key implications and consequences of this kind of misrepresentation are explored.